Analisis Nilai Tambah Usaha Olahan Ikan (Kasus pada Kelompok Pengolah dan Pemasar Dwi Tunggal di Banjar Penganggahan, Desa Tengkudak, Kecamatan Penebel, Kabupaten Tabanan) - MAHARDANA, I PUTU ANDIKA; AMBARAWATI, I.G.A.A.; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.2, April 2015, 2016)
Abstra cts Analysis of Added Value of Fish Processing Business (Dwi Tunggal Processing and Marketing Group in Sub-Village of Penganggahan, Village of Tengkudak, Sub-District of Penebel, Tabanan District). POKLAHSAR Dwi Tunggal is a business group that conducts fish processing such as shredded catfish, fried tilapia, and roasted (pepes) catfish, thus, providing added value of a product. The aim of this study was to calculate the added value obtained from fish processing to become food products and calculate the level of benefits received by POKLAHSAR Dwi Tunggal. The method of analysis in this study used the concept of added value of Hayami and ROI in one year of production. The results showed that shredded catfish provided the highest added value amounting to Rp 61,583.33/ kg of raw materials, followed by roasted catfish and fried tilapia with the respective added value of                       Rp 29,650.00/ kg and Rp 11,380.00/ kg. The highest profit came from the shredded catfish which amounted to Rp 38,250.00/ kg of raw materials, followed by roasted catfish Rp 19,150.00/ kg and fried tilapia Rp 5,780.00/ kg. The total profits obtained by group for the three products from 3,6 tons of raw materials amounting to Rp 43,272,000 in a year. BEP analysis results showed that minimum level of sales (break even point) for roasted catfish was worth Rp 5,195.62 or produced as many as 0.072 kg. Minimum level of sales was as many as 0.059 kg fried tilapia worth Rp 8,892.04 and shredded catfish sales of  Rp 5,997.42 as many as 0.024 kg. Financially, the group already earned a profits; however, it is expected to further increase the amount of production and expand marketing areas. Keywords: added value-, profit, BEP, fish processing